PENGARUH PERSEPSI MEDIA SOSIAL DAN SPONSORSHIP MARKETING TERHADAP POSITIVE WORD OF MOUTH SERTA DAMPAKNYA PADA EKUITAS MEREK (Studi Pada Konsumen Wardah Kosmetik di Media Sosial di Semarang) - Griyana Dewi, Ayu Indira; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2017)
In this fast growing era, internet is no strange to everyone. Whether it’s for individual, corporate, educational, even business interests. Marketing or selling a product throught the internet has become commonplace. Marketing with internet-based strategies,especially social media, can pressing the price of marketing or promotion, but it can reach a large income. Through social media, customers can find information about what they want more easily and freely. One of the biggest brand of cosmetics industry that utilize this strategy is Wardah Cosmetics. As a brand with more than 30 years experience, Wardah should be superior in competition, by building strong brand equity. This study aimed to analyze the variabels of social media perception, sponsorship marketing to positive word of mouth and its impact on brand equity. This study is conducted on Wardah cosmetic’s customer in social media in Semarang.Convenience sampling method is used for this research, samples were collected from 100 respondents (consumer who have instagram account, follow Wardah’s account (@wbhsemarang) and use Wardah products). Multiple regression analysis is used fo this study.This results showed that social media perception and sponsorship marketing has positive and significant effect on positive word of mouth, and positive word of mouth has positive and significant effect on brand equity.